Isolation and Detection of Chikungunya Virus from patients Serum samples using RT- PCR and Real Time RT-PCR - Kamatchiammal, S (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTChikungunya is a viral disease transmitted by Aedes mosquitoes. The disease typically consists of an acute illness with fever, skin rash, and arthralgia. The word chikungunya used for both the virus and the disease means â€œto walk bent overâ€ in some East African languages. Chikungunya is a specifically tropical disease but it is geographically restricted and outbreaks are relatively uncommon. The objective of this study was to develop a rapid detection method to determine of CHIK viral virus in the serum samples collected from chikungunya infected patients in an around Chennai, India. Serum specimens were analyzed for CHIK viral RNA by RT- PCR and Real Time RT-PCR using specific primers. Thirty out of 12 samples were positive for CHIK virus. This result suggests that molecular diagnosis is always having hands higher than the serological diagnosis and viral culture methods. The advantages of RT-PCR and Real Time PCR method adds to early and specific diagnosis of the viral infection before the development of IgM, which is the basis for all the serological assays. The detection procedure used in this study was simple, sensitive and rapid.